2022
DOI: 10.1039/d1ja00392e
|View full text |Cite
|
Sign up to set email alerts
|

A new synthesis scheme of pyrite and chalcopyrite reference materials for in situ iron and sulfur isotope analysis using LA-MC-ICP-MS

Abstract: Microanalysis of Fe and S isotopes in sulfides by laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-MC-ICP-MS) has been used as an important tool to identify the material sources...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…The synthesized pyrite materials PAS-Py600 and natural pyrite Aa018 yielded δ 56 Fe values of 0.18 ± 0.13‰ (2SD, n = 25) and 0.60 ± 0.13‰ (2SD, n = 25), respectively, in good agreement with the recommend values. 59,60 Using Tianyu-Py pyrite as the bracketed standard will, therefore, allow a simple and rigorous comparison of results generated in different laboratories. In addition, an increasing number of studies have shown the significant variability of δ 56 Fe values (∼6‰) in hydrothermal pyrite 38,45 and diagenetic pyrite, 19,34 which is obviously beyond the analytical uncertainty of LA-MC-ICP-MS using a laser spot size of 16 μm.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The synthesized pyrite materials PAS-Py600 and natural pyrite Aa018 yielded δ 56 Fe values of 0.18 ± 0.13‰ (2SD, n = 25) and 0.60 ± 0.13‰ (2SD, n = 25), respectively, in good agreement with the recommend values. 59,60 Using Tianyu-Py pyrite as the bracketed standard will, therefore, allow a simple and rigorous comparison of results generated in different laboratories. In addition, an increasing number of studies have shown the significant variability of δ 56 Fe values (∼6‰) in hydrothermal pyrite 38,45 and diagenetic pyrite, 19,34 which is obviously beyond the analytical uncertainty of LA-MC-ICP-MS using a laser spot size of 16 μm.…”
Section: Resultsmentioning
confidence: 99%
“…The press synthesized pyrite material PAS-Py600 was used as an external standard and the international Fe isotopic standard IRMM-014 (pure iron, 99.9%) from the Institute for Reference Materials and Measurements (IRMM) of the European Commission was used as the quality control sample for in situ Fe isotope analysis. 60 The standard and reference materials were measured before every 10 sample analyses for drift monitoring. The data reduction for LA-MC-ICP-MS analysis was conducted using ISO-Compass software.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations